2015
DOI: 10.15288/jsad.2015.76.117
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Sexual Orientation Disparities in Tobacco and Alcohol Use

Abstract: ABSTRACT. Objective: The purpose of this study was to examine whether the composition of social networks contributes to sexual orientation disparities in substance use and misuse. Method: Data were obtained from the National Longitudinal Study of Adolescent Health (Add Health), a nationally representative cohort study of adolescents (N = 20,745). Wave 1 collected extensive information about the social networks of participants through peer nomination inventories. Results: Same-and both-sex-attracted youths had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
1
19
1
Order By: Relevance
“…The NESARC‐III study was completed in 2013, prior to the 2015 Supreme Court decision to legalize same‐sex marriage, and many states did not have marriage equality laws at the time of the survey. Although we did not find consistent patterns of associations between structural support and TUD and DUD among SM populations, previous research has found greater frequency of TUD and DUD among SM populations is attributed, in part, to higher prevalence of substance use and substance use acceptability in SM social networks, as well as increased perceived tolerant norms and availability of drugs .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The NESARC‐III study was completed in 2013, prior to the 2015 Supreme Court decision to legalize same‐sex marriage, and many states did not have marriage equality laws at the time of the survey. Although we did not find consistent patterns of associations between structural support and TUD and DUD among SM populations, previous research has found greater frequency of TUD and DUD among SM populations is attributed, in part, to higher prevalence of substance use and substance use acceptability in SM social networks, as well as increased perceived tolerant norms and availability of drugs .…”
Section: Discussioncontrasting
confidence: 99%
“…Social support acts as a buffer to stress and is associated with lower victimization and higher resilience against SM‐related discrimination . However, while the relationship between social support and substance use has been extensively assessed among young SM , there has been less research on the impact of social support, and specifically structural and functional support, on SUD among SM adults . Understanding external influences, including social relationships, on substance use among adults is critical to developing effective strategies for reducing SUD.…”
Section: Introductionmentioning
confidence: 99%
“…Supportive communities of drug users (i.e. bonding social networks), such as acquaintances with deviant peers (15,(25)(26)(27)(28) or growing up in a drugfriendly environment may enhance youth substance use (16). These factors are also social resources, which can contribute to behaviours that do not enhance health and positive outcomes.…”
Section: Social Capital and Youth Substance Usementioning
confidence: 99%
“…Peer pressure plays a major role in the development and continuation of substance use during adolescence and early adulthood (41)(42)(43)(44)(45)(46)(47)(48)(49), and peer substance use is described as a necessary condition and a key explanatory variable for adolescent substance misuse (28,50,51). Overall, peer network has also been described as a factor of increased substance use behaviours (26).…”
Section: Social Capital and Youth Substance Usementioning
confidence: 99%
See 1 more Smart Citation